Lower urinary tract injuries in patients with pelvic fractures at a level 1 trauma center – an 11-year experience. (2nd November 2023) - Rehné Jensen, Lasse; Røder, Andreas; Possfelt-Møller, Emma; Singh, Upender Martin; Aagaard, Mikael; Evald Nielsen, Allan; Svendsen, Lars Bo; Penninga, Luit
Abstract: Background: Urological injuries can occur in patients with pelvic fractures. Treatment recommendations lack solid evidence and is often pragmatical. There is a continuous need to describe short- and long-term morbidity following lower urinary tract trauma. Objective: To describe incidence, diagnosis, treatment, and morbidity following lower urinary tract injuries in pelvic fractures. Patients and methods: Retrospective study including patients with pelvic, including acetabular, fractures admitted to a Level I Trauma Centre covering 2.8 million citizens between 2009 and 2020. Outcome measurements comprised primary management, treatment trajectory, short- and long-term complications and outcomes. Results: A total of 39 (5%) patients with pelvic fractures had concomitant urethral and/or bladder injuries, and one patient with an acetabular fracture had a bladder injury. The management of urethral injuries varied vastly, and complete urethral ruptures were associated with severe short- and long-term complications. Only one patient with bladder injury experienced severe long-term complications. Conclusions: Management of lower urinary tract injuries in patients with major pelvic fractures remains a major challenge. Special attention should be focused on urethral injuries where we uncovered an unsystematic treatment and follow-up even in a highly experienced centre, although this is also attributed to complicated multidisciplinary patient trajectories. There is a continuous need to reduce long-term complications following urethral trauma which should be addressed in multicenter studies.